A Power-Efficient Co-designed Out-of-Order Processor - Deb, Abhishek; Codina, Josep Maria; González, Antonio (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2011)
A co-designed processor helps in cutting down both the complexity and power consumption by co-designing certain key performance enablers. In this paper, we propose a FIFO based co-designed out-of-order processor. Multiple FIFOs are added in order to dynamically schedule, in a complexity-effective manner, the micro-ops. We propose a commit logic that is able to commit the program state as a superblock commits atomically. This enables us to get rid of the Reorder Buffer (ROB) entirely. Instead to maintain the correct program state, we propose a four/eight entry Superblock Ordering Buffer (SOB). We also propose the per superblock Register Rename Table (SRRT) that holds the register state pertaining to the superblock. Our proposed processor dissipates 6% less power and obtains 12% speedup for SPECFP, as a result, it consumes less energy. Furthermore, we propose an enhanced steering heuristic and an early release mechanism to increase the performance of a FIFO based out-of-order processor. We obtain performance improvement of nearly 25% and 70% for a four FIFO and for a two FIFO configurations, respectively. We also show that our proposed steering heuristic based processor consumes 10% less energy than the previously proposed steering heuristic.